2003
DOI: 10.1007/s00421-002-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of whole-body vibration on maximal voluntary isometric knee extensor force and rate of force rise

Abstract: Whole-Body vibration (WBV) may lead to muscle contractions via reflex activation of the primary muscle spindle (Ia) fibres. WBV has been reported to increase muscle power in the short term by improved muscle activation. The present study set out to investigate the acute effects of a standard WBV training session on voluntary activation during maximal isometric force production (MVC) and maximal rate of force rise (MRFR) of the knee extensors. Twelve students underwent a single standard WBV training session: 5x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
113
5
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 7 publications
11
113
5
11
Order By: Relevance
“…On the other hand, our data differ with those reported by Bullock et al (11), who used a duration of 60 seconds and also found no changes in jump height (SJ and CMJ) in a group of 7 elite skeleton athletes. In the study, authors used a recovery time of 3 minutes between sets, which has been deemed excessive (20). Adams et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, our data differ with those reported by Bullock et al (11), who used a duration of 60 seconds and also found no changes in jump height (SJ and CMJ) in a group of 7 elite skeleton athletes. In the study, authors used a recovery time of 3 minutes between sets, which has been deemed excessive (20). Adams et al…”
Section: Discussionmentioning
confidence: 99%
“…We used the combination of parameters determined to be the most effective by previous studies: a frequency of 30 Hz (14,19) and a recovery time of 2 minutes between sets for both studies (20). Because of the mechanical characteristics of the machine used, peak-to-peak displacement was fixed as 4 mm; greater muscle activity and strength were attained when this displacement was combined with the aforementioned frequency (1,19,20). Vibration was applied using a vibrating platform producing sinusoidal oscillations (Nemes, Ergotest, Rome, Italy).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that whole-body vibration (WBV) training, in which subjects perform unloaded exercises on a vibrating platform, resulted in improved muscle strength or muscle performance (3,11,19,20,24,25). Some other studies reported no changes in muscle strength after WBV training (9,10).…”
mentioning
confidence: 99%